Characteristics of Mucormycosis in Hematological Patients and a Death Prediction Model - Ma, Xiaoxu; Li, Ang; Cao, Weijie; Li, Huiling; Zhang, Suping; Li, Li; Xing, Haizhou; Tian, Wenliang; Jiao, Pengfei; Chen, Jiajun; Zhang, Qingxian; Xu, Aiguo; et al. (Frontiers in Microbiology, 2021)
Mucormycosis is an angio-invasive fungal infection, associated with high mortality. The aim of our study was to explore the high risk factors and predict the death of hematological disease complicated with mucormycosis. We retrospectively analyzed clinical data of 31 patients with hematological disease complicated with mucormycosis, adopted random forest to establish the death prediction model, and validated the model in another 15 patients. The median age of the 31 cases was 46 (28-51) years, male to female ratio 1.38:1 and 90-day mortality rate 54.8%. The most common underlying disease was acute myeloid leukemia (58.1%). The main clinical symptoms were fever (100%), cough (87.1%), sputum (80.6%), chest pain (61.3%) and hemoptysis (19.4%). Reversed halo sign (83.9%) was the most common computed tomography sign. 48.4% of patients also had aspergillus or bacterial infections. Discriminative models were constructed by random forest with 17 non-survivors and 14 survivors. Procalcitonin, the duration of intravenous administration of amphotericin B or amphotericin B liposomes and neutropenia at death or 90 days of survival were the leading risk factors for poor prognosis, with area under the curve (AUC) of 0.975 (95%CI 0.934–1). We chose 0.6775 as death prediction threshold (with 82.3% sensitivity and 100% specificity) and validated the model successfully in another 15 patients. Chest pain and reversed halo sign are specific clinical and image signs of hematological disease complicated with mucormycosis. Neutropenia, elevated procalcitonin, insufficient use time of amphotericin B or amphotericin B liposomes are risk factors for death.